Домінанти третьої інтелектуальної революції та завдання сучасної освіти - Дольська, Ольга Олексіївна (Мелітопольський державний педагогічний університет ім. Богдана Хмельницького, 2015)
У центрі уваги - розмова про інтелектуальні революції людства. Автор окреслює деякі основні напрями розвитку практичної діяльності в сучасному освітньому просторі. Кожен з них опосередковано або прямо грунтується на футурологічних прогнозах.

In the centre of attention there is a talk about intellectual revolutions of mankind. Reflections of the author embrace various research that help generalized and integral study of the processes that either directly or indirectly affect the intellectual and cognitive changes. Within eyeshot,along with a new scientific paradigm, there are findings and research of modern futurologists. The whole complex of various innovations creates a complete foundation for a new intellectual revolution. Therefore, educators ought to introduce changes in the field of education and follow its innovations. The author outlines some basic directions of practical activity development in modern educational space. Each of them either indirectly or directly is based on the futuristic forecast.
Dominants of the third intellectual revolution and tasks of modern education
Keywords: інтелектуальна революція; наповнення дисципліни; автодидактика; лідерство; intellectual revolution; future of humanity; educational technology; content load of subjects; autodidactics; leadership